2008
DOI: 10.1002/j.2050-0416.2008.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Free, Soluble Ester and Insoluble-Bound Phenolic Compounds in Different Barley Varieties and Corresponding Malts

Abstract: S Ten different barley cultivars and their corresponding malts were used to obtain different fractions. Phenolics extracted belonged to free, soluble esters and insoluble‐bound fractions. Total phenolic content (TPC) of the free fraction, as measured according to the Folin‐Ciocalteu method, ranged from 37.7 to 167.2 mg gallic acid equiv/kg of dried material (GAE/kgdw) for barley and between 34.1 and 72.3 mg GAE/kgdw for malt. The bound phenolic content ranged from 210.3 to 320.5 and between 81.1 and 234.9 mg G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 25 publications
(23 reference statements)
4
78
1
2
Order By: Relevance
“…The values of TPC depended on variety, growing area and least use of fertilizers. TPC was in accordance with data already published 6 .…”
Section: The Content Of Total Polyphenolssupporting
confidence: 73%
See 2 more Smart Citations
“…The values of TPC depended on variety, growing area and least use of fertilizers. TPC was in accordance with data already published 6 .…”
Section: The Content Of Total Polyphenolssupporting
confidence: 73%
“…Several types of polyphenol extraction have been described 6,7,11,19,22,23,26,29 . The mixture of water with organic solvent is one of the most used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, McCarthy and co-workers (2012) recently reported that black BSG extracts exhibited the highest phenolic content. This difference can partially be explained by the type of malt used in the brewing process which has been shown to interfere with the content of individual phenolic compounds extracted (Dvořáková et al, 2008;Magalhães et al, 2011). In addition, this difference can also be due to the melanoidins generated during kilning by the Maillard reaction, whose content increases with KT.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…During malting, a significant decrease of bound phenolics takes place with a corresponding increase of soluble esterified fraction (Dvořáková et al 2008b). This can be explained by the enzymatic release of the bound antioxidants of barley as well as glycosylation reactions during malting and non-enzymatic changes during kilning.…”
mentioning
confidence: 99%